Efficiency and Profitability of Rice Farming: Comparison of Transplanting (TAPIN) and Direct Seeding (TABELA) Systems - Moh. Shofiyur Rohman; Rosihan Asmara; Fahriyah Fahriyah (The University of Lampung, 2025)
Farmers play an essential role in producing food and meeting the community's food needs. However, they often face various obstacles and challenges in efforts to increase crop yields to boost agricultural income. One approach to increasing agricultural productivity is by understanding the Efficiency and Profitability of Rice Farming with the transplanting system (TAPIN) and the direct seeding system (TABELA) in Padang Mentoyo Village, Kapas District, Bojonegoro Regency. This study used the Data Envelopment Analysis (DEA) method, with 74 respondents consisting of 37 TAPIN farmers and 37 TABELA farmers, to determine the level of efficiency and profitability between TAPIN and TABELA. The results showed that TABELA farmers are more efficient than TAPIN farmers because as many as 97.3% of TABELA farmers are included in the High and Full Efficient categories. This is because implementing the TABELA system is able to reduce the time needed to move seedlings, so that the planting process is faster. Keywords: Direct seeding system (TABELA), Transplanting system (TAPIN), Rice farming income, Yield.